The role of social marketing in health education / Ismail Sualman - Sualman, Ismail (Universiti Teknologi MARA Cawangan Pulau Pinang, 2003)
Abstract: While social marketing is flourishing, there appears to be confusion regarding what it is, what it can reasonably do, and how it should be applied to health education. Some confusion relates to a perception that social marketing is limited to narrow strategies, interventions, or theories. The purpose of this paper is to position social marketing as a systematic planning process similar to those used in health education. The paper describes why social marketing is a planning process, how it compares and contrasts to health education planning models, and how the social marketing planning framework may benefit health education practice.